The 10 November Ceasefire Agreement in the Nagorno-Karabakh Prolonged Conflict: First Step Towards Settlement or New Freezing? - Luminița CIOBANU (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene, 2021)
The common declaration signed by the Presidents of Russia and Azerbaijan and the Prime Minister of Armenia on November 9, 2020, put an end to the one month and a half military clashes that had taken place in the Nagorno-Karabakh conflict zone (Nagorno-Karabakh proper and the seven adjacent districts surrounding it) since September 27, 2020. The entry of the Russian troops into the region represents, in fact, a new “frozening” of the conflict on the new alignments of the troops (which are becoming the new “Line of Contact”), for an indefinite period of time. While Azerbaijan has fulfilled most of its objectives, taking back the seven adjacent districts and the southern part of NagornoKarabakh proper, it has not succeeded in taking back Nagorno-Karabakh entirely. Moreover, the status of Nagorno-Karabakh remains undetermined, which also leaves room to further tensions and/or negotiations.